2016
DOI: 10.1080/15622975.2016.1259498
|View full text |Cite
|
Sign up to set email alerts
|

sVCAM-1, sICAM-1, TNF-α and IL-6 levels in bipolar disorder type I: Acute, longitudinal and therapeutic implications

Abstract: BD is related to both acute and long-term alterations of immune mediators, including adhesion molecules. The potential immunomodulatory role of pharmacotherapeutic treatment is also to be considered in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 52 publications
2
22
1
Order By: Relevance
“…It is of particular interest in psychiatric disorders for two reasons: It has a key function for the blood-brain barrier, which plays an important role in the biology of psychiatric disorders, and it is a marker for in ammation [38]. High soluble ICAM (sICAM) levels were found during both the depressed and the manic states and also during the euthymic phase in bipolar disorder [39].…”
Section: Discussionmentioning
confidence: 99%
“…It is of particular interest in psychiatric disorders for two reasons: It has a key function for the blood-brain barrier, which plays an important role in the biology of psychiatric disorders, and it is a marker for in ammation [38]. High soluble ICAM (sICAM) levels were found during both the depressed and the manic states and also during the euthymic phase in bipolar disorder [39].…”
Section: Discussionmentioning
confidence: 99%
“…One study found a weak positive correlation between sICAM-1 levels and the scores on the Yale Mania Rating Scale in patients in a manic state (Turan et al, 2014). In their study in patients with bipolar disorder (n = 83), another group of researchers described higher blood levels of sICAM-1 (and higher IL-6, but lower tumor necrosis factor-α and lower sVCAM) in both acute and remission phases of the disorder than in age-, sex-, and body-mass–matched healthy controls (n = 73) (Pantovic-Stefanovic et al, 2016). Similarly, another study found significantly higher blood levels of sICAM-1 in euthymic bipolar patients than in healthy controls (Reininghaus et al, 2016).…”
Section: Icam-1 In Psychiatric Disordersmentioning
confidence: 99%
“…The cytokine network is activated to produce a large number of cytokines closely related to the development of inflammation in sepsis patients [4,5]. Among the inflammatory mediators involved, tumor necrosis factor alpha (TNF-α) is the closest mediator of the cytokine cascade.…”
Section: Introductionmentioning
confidence: 99%